Measurement of activity of 131I deposited in human thyroid during the medical examination - Filipiak, Bogdan; Ośko, Jakub; Golnik, Natalia; Pliszczyński, Tomasz; Haratym, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2002)
The aim of our activity was: the creation of a new model of thyroid calibration phantom and working out the method of calibration measurement sets for determination of total activity of 131 I deposited in thyroid of people who are occupational exposured on contamination of 131 I or during medical examination in which this radioisotope was used. A new kind of aquatic, neck phantom has been constructed in which the thyroid glands are simulated by two cylindrical vessels, 13 cm 3 each. Those glands are able to change their position - fluently in horizontal and vertical way. We have made a few sets of calibration measurements for different effective depths of thyroid glands (in sphere between 24 to 60 mm), keeping a standard distance between detector and a patient's neck area. Basing on the results of those measurements we have also worked out the methodology of determination of effective depth of thyroid, using the measured gamma spectra. In effect we have got a possibility of estimating 131 I radioisotope activity deposited in thyroid, independently from its effective depth. After that, we have performed several measurements to estimate errors followed by uncertainty of geometry measurements. 95 patients from one of Warsaw hospitals were examined using mentioned measuring method. In over 96% of them total activity in thyroid was valued as a higher, (about middling 7%), than at ones who had been examined by different method which didn't take into account the position of thyroid.